Influence of Nitrogen on Growth Performance, Cut Flower Characteristics and Corm/Cormel Production of Gladiolus - Baral, SP; Baral, DR; Gautam, DM; Pun, UK (Nepal Journal of Science and Technology, 2013)
A study was carried out to access the influence of nitrogen level (100, 150, 200, 250, 300 kg/ha) on growth performance, cut flower characteristics and corm/cormel production of three varieties (American beauty, Interpret and Candyman) of gladiolus (Gladiolus hybrida L.) in the farmer’s field at Gunjanagar VDC, Chanauli, Chitwan, during September, 2010 to April, 2011. The experiment consisted of 15 treatment combinations laid out in 2 factorial randomized complete block design (RCBD) with 4 replications. Nitrogen levels significantly influenced growth performance, cut flower characteristics and corm/cormel production of gladiolus. Increasing the level of nitrogen up to 200 kg/ha, increased the rate of sprouting (97.33%), number of sprout/corm (2.05), taller plant (106.7cm) with more number of leaves (9.85), longest spike(86.58cm) with more number of florets/spike (16.73) were produced. Moreover, largest spike (92.62 g weight) having thicker (1.14 cm girth) and longest rachis (54.5 cm) were produced by 300 kg/ha. Size of daughter corm (5.8 cm) was highest with 300 kg/ha while number of the cormels per plants (89.45) was highest at 200 kg/ha nitrogen. Among three varieties, Candyman performed better with respect to early days to sprouting (15.1), early days to 50% sprouting (23.1), higher total sprouting percentage (97.6%), more number of leaves/plant at harvest (10.76), highest plant height (136.8 cm) at harvest, highest length of spike (81.6 cm), more weight of spike (81.78 g), thicker spike (1 cm) and longest rachis (51.1 cm). Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 25-31 DOI: http://dx.doi.org/10.3126/njst.v13i1.7395